Theoretical and methodological prerequisites for the application of multimedia teaching materials in professional preparing for a future music teacher - Bondarenko, A.V. (Pedagogy of Higher and Secondary Education, 2009)
The article considers the possibilities of using multimedia teaching aids in terms of taking into account the peculiarities of scientific and artistic creativity.